2008
DOI: 10.1002/tea.20241
|View full text |Cite
|
Sign up to set email alerts
|

Girls and science: A review of four themes in the science education literature

Abstract: Despite valuable syntheses of the field of gender and science education, there has not been a systematic, comprehensive review of the literature on gender and science education in recent years. We examine the literature pertaining to girls' engagement in science and develop four themes (equity and access, curriculum and pedagogy, the nature and culture of science, and identity) that we believe provide a coherent picture of the different kinds of approaches happening currently, while at the same time allowing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
235
1
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(286 citation statements)
references
References 126 publications
10
235
1
16
Order By: Relevance
“…5 Brotman and Moore (2008) provide an overview of within-sch ool processes identified in the science education literature that might lead to genderdifferentiated likelihoods of majoring in STEM or persist ing with STEM coursework . At the college level, an experimental study by Loge l et al (2009) showed that young women's interactions with men can negatively affect their performance in engineering.…”
Section: Pipeline and Life Course Modelsmentioning
confidence: 99%
“…5 Brotman and Moore (2008) provide an overview of within-sch ool processes identified in the science education literature that might lead to genderdifferentiated likelihoods of majoring in STEM or persist ing with STEM coursework . At the college level, an experimental study by Loge l et al (2009) showed that young women's interactions with men can negatively affect their performance in engineering.…”
Section: Pipeline and Life Course Modelsmentioning
confidence: 99%
“…No entanto, ao analisar os gêneros e os tratamentos (PI e não PI), os autores encontraram que os homens do grupo que não usaram o PI tiveram um ganho significativo na regulação da cognição, enquanto no caso das mulheres, foi o grupo que usou o PI que apresentou ganho na regulação da cognição. Segundo esses autores, tal resultadoé coerente com a literatura dá area que afirma que mulheres preferem ambientes colaborativos de ensino [99].…”
Section: Metacogniçãounclassified
“…Looking at the field of science education research and the main research topics within this field, gives at hand that this kind of research contributes only to a minority part of the whole, and what is obvious for us obviously is not that obvious for a majority of the researchers in the field. When science education researchers have studied gender as a category, they conceptualized gender as an individual trait, rather than from a social context (Nyström 2007) and many studies are restricted to comparing female and male students on variables such as students' achievement, participation, engagement, and attitudes towards science (Brotman and Moore 2008). Those who have placed attention on the relevance of gender issues in the teaching of science, often through a critical assessment of the subjects as such, have used different feminist theories as a starting point.…”
mentioning
confidence: 99%